Social media for social good? A thematic, spatial and visual analysis of humanitarian action on Instagram. Issue 13 (3rd October 2021) - McCosker, Anthony; Kamstra, Peter; De Cotta, Tracy; Farmer, Jane; Shaw, Frances; Teh, Zoe; Soltani Panah, Arezou
ABSTRACT: As an image and location sharing platform, Instagram offers intimate visual access to events, experiences and situations in a manner that is mobile and contextual. Partnering with Australian Red Cross, this paper develops a mixed methodology for using Instagram data to identify and understand individuals' everyday humanitarian activity in a major urban centre (Melbourne, Australia) outside of the temporal frame of crisis. The research integrates hashtag data collection with thematic analysis in a Geographic Information System (GIS) to use visualise the links between types of humanitarian action, their motivations and contextual situations to precise urban locations. These attributes of Instagram posting practices offer a base layer of information about disparate prosocial action taking place in an urban context. We see this as informing and sustaining a new hybrid mode of promotional and humanitarian communication, evidencing social good 'place making' and enabling new forms of visible humanitarian participation.